Associations Between Being ‘Locked-In’ and Health – An Epidemiological Study - Aronsson, Gunnar; Taloyan, Marina; Westerlund, Hugo; Östergren, Per-Olof (Nordic Journal of Working Life Studies, 2019)
Objective. The aim of this study was to investigate associations between an individual’s level of perceived control over labor market position (locked-in and not locked-in) and self-rated health and psychological well-being. Methods. A representative sample (n = 11,675) of the working population in southern Sweden responded to a questionnaire. Results. Sixty-seven percent of the respondents worked in their preferred workplace and occupation. Nineteen percent reported being in a nonpreferred workplace and nonpreferred occupation (double locked-in). Twenty-three percent reported suboptimal health compared with 31% among the double locked-in. The risk of suboptimal health was elevated in all locked-in groups also after adjustment for background variables and job strain. In the double locked-in group, the fully adjusted odds ratio for suboptimal health was 1.72 (95% confidence interval 1.49–1.99) and for suboptimal psychological well-being 2.17 (95% confidence inter val 1.84–2.56). Odds ratio for the other locked-in groups was lower but still statistically significant. Conclusions. Being at a nonpreferred work-place or occupation was associated with impaired health.